Phase transition and crystallization behavior of grafted starch nanocrystals in PLA nanocomposites - Somayeh Sharafi Zamir; Babak Fathi; Abdellah Ajji; Mathieu Robert; Said Elkoun (eXPRESS Polymer Letters, 2022)
Polylactic acid (PLA) has shown two different crystalline structures, namely α and α′ when cooled down from the melt state. However, α-PLA has shown significant improvement in the barrier and mechanical properties of PLA. Although the effect of some nucleating agents on phase transformation of the PLA has been determined in the past, this is the first attempt, the effect of the starch nanocrystals on the formation of polymorphic crystal structure of PLA was evaluated. In this framework, the effect of lactic acid grafted starch nanocrystals (SNCs-g-LA) concentrations on the phase transition, and crystallization behavior of PLA/SNCs-g-LA nanocomposites at different isothermal crystallization temperatures (Tc) were studied. The results indicate that SNCs-g-LA nanoparticles promote the degree of crystalline transition to yield the highly crystalline ordered α-PLA. Further, the half-time crystallization (t1/2) of PLA composites was calculated by the Avrami equation. The t1/2 of PLA was minimum by adding 5 wt% SNCs-g-LA nanoparticles, and it decreased from 10.4 to 3.9 min. The growth rate of the spherulite morphology of PLA composites showed a significant improvement in the crystalline structure of PLA/SNCs-g-LA (5 wt%) nanocomposites as well. Finally, small angle X-ray scatting (SAXS) analysis showed that the inclusion of 5 wt% grafted SNCs resulted in the increment of the long period (Lac) as well as crystal layer thickness (Lc).